MACAM-MACAM RESTORASI RIGID PASCA PERAWATAN ENDODONTIA - Dwi Warna Aju Fatmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Restorative materials is one of materials that always be used in dentistry. Restorative materials can improve and restore damaging tooth structure. Restorative materials can be devided in two groups. Those were plastic and rigid restorative. All of restorative materials have special properties, so they have different advantage anddisadvantage. Aim of this study is to inform about rigid restorative post endodontic treatment. Rigid restorative can be made in out oral cavity and cemented.